Pengaruh Waktu Pemeraman Terhadap Uji Kuat Tekan Paving Block dari Campuran Tanah dengan Semen Menggunakan Alat Pemadatan Modifikasi - Septian, Risqon; Iswan, Iswan; Setyanto, Setyanto (Universitas Lampung, 2016)
Paving block is a building material composition made of a mixture of Portland cement or other similar hydraulic adhesive material, water, and aggregates or without other additives that do not reduce the quality of the concrete. In the implementation, paving blocks are made of basic materials such as cement, sand, aggregates and water by mixing all the ingredients and printing the mortar of paving block. One of the efforts to create new innovations in appliance manufacture of paving blocks so that paving blocks compactor was created which were expected to improve the quality of the paving block with the basic mixture of cement and soil.Soil samples tested in this research were soils derived from Kota Baru, Lampung Selatan. Content mixture used was 20% and conducted from 7 days, 14 days, 21 days, and until 28 days curing time as well as the pre and post-combustion treatment on the sample of paving blocks. Based on the physical properties of soil testing, USCS classifies the soil samples as fine-grained soils and belongs to CL group.The results of the research showed that the manufacture of paving blocks using the clay materials with additive materials such as cement fulfilled paving block SNI-03-0691-1996. The addition of the additive materials and curing can increase the physical and mechanical properties of the soil. For the compressive strength of paving blocks without and with burning process were best shown in the addition of a mixture of 20% content with curing time to 14 days. Beside the compressive strength, overall the water absorption between 3-9% qualifies paving block SNI-03-0691-1996. Keywords: paving blocks, clay, compressive strength, curing time, water absorption.